1996
DOI: 10.1183/09031936.96.09112346
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors associated with use of home nebulized therapy for COPD

Abstract: P Ps sy yc ch ho ol lo og gi ic ca al l f fa ac ct to or rs s a as ss so oc ci ia at te ed d w wi it th h u us se e o of f h ho om me e n ne eb bu ul li iz ze ed d t th he er ra ap py y f fo or r C CO OP PD D ABSTRACT: This study examined the relationship between adherence to domiciliary nebulized therapy and psychological factors; patient attitudes, anxiety, depression, and quality of life. Ninety three patients aged 45-77 yrs with chronic obstructive pulmonary disease (COPD) and using domiciliary nebulizers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
1
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 15 publications
4
76
1
6
Order By: Relevance
“…15 The included studies originated from Canada and the United Sates, 16 Hungary, 17 Japan, 15,18 The Netherlands, 14 and the United Kingdom. 12,13 The population size varied between 11 12 and 985 16 subjects, with a mean age of 58 14 to 76 15 y. The general characteristics of the reviewed studies are presented in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…15 The included studies originated from Canada and the United Sates, 16 Hungary, 17 Japan, 15,18 The Netherlands, 14 and the United Kingdom. 12,13 The population size varied between 11 12 and 985 16 subjects, with a mean age of 58 14 to 76 15 y. The general characteristics of the reviewed studies are presented in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…12,13, 16 Turner et al 16 and Bosley et al 12 used a self-reported questionnaire and electronic monitoring for measuring adherence simultaneously, but both groups considered the subjects to be adherent based on the results of the electronic monitoring only. Except for the studies conducted by Mochizuki et al 15 and Bosley et al, 12 most studies defined adherence as a dichotomous variable.…”
Section: Medication Adherence and Hrqolmentioning
confidence: 99%
See 3 more Smart Citations